2004
DOI: 10.1002/asi.20052
|View full text |Cite
|
Sign up to set email alerts
|

Finding governmental statistical data on the Web: A study of categorically organized links for the FedStats topics page

Abstract: More than 100 U.S. governmental agencies offer links through FedStats, a centralized Web site that facilitates access to statistical tables, reports, and agencies. This and similar large collections need appropriate interfaces to guide the general public to easily and successfully find information they seek. This paper summarizes the results of 3 empirical studies of alternate organization concepts of the FedStats Topics Web page. Each study had 15 participants. The evolution from 645 alphabetically organized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…Our observations were consistent with earlier results indicating the importance of informative, well-designed link text (Ceaparu and Shneiderman, 2004). As screen-reader users often do not listen to the entire text of a link, pertinent terms should be placed as early as possible in links (Theofanos and Redish, 2003).…”
Section: Implications For Designsupporting
confidence: 93%
“…Our observations were consistent with earlier results indicating the importance of informative, well-designed link text (Ceaparu and Shneiderman, 2004). As screen-reader users often do not listen to the entire text of a link, pertinent terms should be placed as early as possible in links (Theofanos and Redish, 2003).…”
Section: Implications For Designsupporting
confidence: 93%
“…They were classified into: census, vital registration, survey, estimation/projection/modeling, service/ surveillance and administrative records [[14]]. 31 sources (63%) were found on government sites, and only 13 sources (26%) and 17 sources (35%) were found on non-government and international sites (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research (Card et al 2001, Blackmon et al 2002, Brumby and Howes 2008 has demonstrated that people have lower success rates and require more time to complete the task when they are presented with weak scent compared to high scent. Ceaparu and Shneiderman (2004) report study results in which users' performance nearly doubled and frustration levels dropped when the wording of link-labels was changed.…”
Section: Introductionmentioning
confidence: 94%